Effect of interfacial surface preparation technique on bond characteristics of both NSC-UHPFRC and NSC-NSC composites. (February 2021) - Mansour, Walid; Fayed, Sabry
Abstract: Ultra-high performance fiber reinforced concrete (UHPFRC) reveals superior mechanical properties that make it suitable for the strengthening/rehabilitation of normal strength concrete (NSC) structures. This paper investigates the effects of the interfacial surface preparation's methods on the bond performance for both the NSC-UHPFRC and the NSC-NSC composites. The interfacial bond characteristics of five surface preparation methods were studied, i.e., the fair face, the wire brushed surface, the use of the colloidal glue and the x-wrap epoxy on both the fair face and the wire brushed surfaces in addition to the drilled holes and grooves with different areas by using the slant shear, the splitting tensile and the direct shear bond tests. The results indicated that the overall interfacial performances of the NSC-UHPFRC composites were better than their NSC-NSC counterparts because the viscous UHPFRC material can fill the pores and the concaves on the NSC surface causing shear connectors able to enhance the bond performance. The bond strengths of the fair face composites could not achieve the acceptable minimum requirements specified by the ACI 546-06 in contrast to the wire brushed specimens. The area of the drilled holes and grooves had a significant effect on the bond performance and the failure patterns of the tested composites. The recorded splitting tensile bond strength level of the drilled holes and grooves composites categorized as an "Excellent" bonding. The cohesion and the friction parameters of the all tested composites with the proposed interfacial preparations methods achieved the acceptable limits specified by the AASHTO (2010).